Unidade de ensino potencialmente significativa para estudo de estatística no Ensino Fundamental II - Santos, Scheila Montelli dos (2018)
The present text refers to the master's thesis allocated in the research areas of Theoreticalmethodological Foundations for the teaching of Sciences and Mathematics and its main objective is to analyze the implementation of a Potentially Meaningful Teaching Unit –(PMTU) to approach the content of Statistics in Elementary Education, evaluating their relevance in didactic terms and as favoring the construction of statistical concepts. The issue leading to present study lay in the identification of poorly taught Statistics, particularly in Elementary Education II, thus pointing to the necessity to propose methodological alternatives. Such a need sought a subsidy in the Meaningful Learning Theory of David Paul Ausubel, which asks the following question: what potential does a didactic proposal regulated by the Meaningful Learning Theory offers for the construction of statistical concepts? To answer this question the study considers the development of a didactic sequence in the form of PMTU following the structure proposed by Moreira (2011b) and relying on trends in mathematics teaching, the guidelines of the Brazilian National Curricular Parameters, the Common National Base Curriculum and studies linked to Education in Statistics. This didactic sequence, in the form of PMTU, was developed over 20 meetings in a Public Elementary School's Seventh grade located in the Rio Grande do Sul. Methodologically, the research proposed in this study is characterized as a qualitative approach and in terms of their goals as participant research.Records were used as a tool for data collection in the logbook of the researcher, a class teacher, and materials produced by students during meetings, in particular the diagnostic evaluation and the summative evaluation carried out in the first and penultimate meetings respectively. Discussions about results obtained from the study of the Meaningful Learning Theory and the foundations of the PMTU, complemented by other discussions in particular those by studies involving the field of Statistical Education. This discussion used two categories - Didactic Strategies and Educational Objectives, divided into subcategories; these categories allowed to identify that the PMTU in didactic terms proved to be an important tool favoring motivation, involvement, participation and the search for knowledge. Regarding educational objectives, the PMTU demonstrated its potential in terms of activating previous knowledge and confronting new knowledge. The present dissertation is accompanied by an educational product developed with the objective of providing didactic-methodological subsidy to elementary school teachers II. This educational product is integrated by the developed didactic sequence (PMT U) and is available digitally and with free access.